Global Cytopathology-Hematopathology Practice Trends: A Cyto-Heme Interinstitutional Collaborative Practice Survey of Intradepartmental Collaboration and Challenges in Pathology. Issue 2 (11th September 2021) - Zadeh, Sara L; Balassanian, Ronald; Cheung, Matthew C; Falchi, Lorenzo; Hasserjian, Robert; Lin, Oscar; Long, Steven R; Ly, Amy; Menke, Joshua R; Mou, Eric; Natkunam, Yasodha; Ruiz-Cordero, Roberto; et al.
Abstract: Objectives: Small-volume biopsy—fine-needle aspiration biopsy (FNAB) with or without core biopsy—is in increasing use in diagnosis and management of lymphoma patients. Our objective was to survey the current practice in small-volume biopsy diagnosis of lymphoma, focusing on the interaction among hematopathologists and cytopathologists and the integration of FNAB, core biopsy, and flow cytometry studies at sign-out. Methods: This study used a cross-sectional survey design employing the RedCap database distributed via nine pathology professional society email listservs. The survey consisted of 25 multiple-choice questions and several free text fields. In total, 128 pathologists participated. Results: Most respondents indicated that FNAB specimens in which lymphoma is a diagnostic consideration (FNAB-L) are seen daily or weekly (68/116; 58.6%). However, most institutions have separate hematopathology and cytopathology services (72/116; 62.1%) with inconsistent communication. When communication occurred, respondents were frequently inclined to reconsider their original diagnoses. Barriers identified included lack of communication, inadequate access to diagnostic studies, no formal subspecialty training, and various opinions regarding FNAB in diagnosing lymphoma. Conclusions: This survey showed that FNAB-L specimens are common, with a lack of uniformity in how complementary fine-needle aspiration and core biopsy specimens or flow immunophenotyping results are shared across hematopathology and cytopathology services.